Pengaruh Perbandingan Konsentrasi Asam Sitrat-Malat terhadap Karakteristik Granul Effervescent Daun Katuk (Sauropus androgynus L. Merr) - Made Yuni Cahya Ningrum; Gusti Ayu Kadek Diah Puspawati; I Gusti Ayu Ekawati (Department of Food Science and Technology Study Program, Faculty of Agricultural Technology, Udayana University, 2022)
The purposes of this research was to determine the effect of concentration ratio of citric-malic acid on the characteristics of the effervescent granule of katuk leaves and to proper concentration ratio of citric-malic acid to get the effervescent granule of katuk leaves with the best characteristics. The research used Completely Randomized Design (CRD) with the treatment of concentration ratio of citric-malic acid consisting of 5 levels: 5% : 25%, 10% : 20%, 15% : 15%, 20% : 10%, dan 25% : 5%. The treatment was repeated 3 times in order to obtain 15 experimental units. The data were analyzed statistically using the variance test and if the treatment had a significant effect to observed variables, it was continued with Duncan's Multiple Range Test. The result showed that concentration ratio of citric-malic acid had a significant effect (P<0,05) on moisture content, ash content, flow time, soluble time, high foaming, total flavonoids, and antioxidant capacity. The concentration ratio of 5% citric acid and 25% malic acid was the best treatment to produce effervescent granule of katuk leaves with the moisture content 5.67%, ash content 23.84%, pH 5.88, soluble time 20.69 seconds, flow time 0.80 seconds, high foaming 3.20 cm, total flavonoids 21.04 mgQE/100g powder, antioxidant capacity 16.51 mgGAEAC/100g powder sensory hedonic of the color was liked, the aroma was liked, the taste was liked and the overall acceptance was liked.